(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Basically, all hydraulic performance systems are extremely reliant on the rising of the oil temperature, due to an increase in the pressure, decrease lubricate moving parts, increases leakage and dissipate heat. This could lead to the variation in bulk modulus of elasticity for different working cnditions, which could be affected in the performance of the system. Accordingly, an attempt was made to examine the effect of the bulk modules of elasticity on the accurate position. Six pressure suppliers were critically used (20, 30, 40, 50, 60 and 70) bar at five oil temperatures (25, 40, 50, 60 and 70) °C. Experimental results showed that the maximum variation percentage in the actuator displacement at the same load occurred at 70 °C oil temperature and there were 4.252%, 7.25% , 9.154% , 9.253%, 8,727%, 15.476 and 19.23% in 20 , 30, 40, 50, 60 and 70 bar pressure supply, respectively.